The Influence of the Implementation of Regional Government Information Systems and Internal Government Control Systems on the Quality of Financial Reporting - Naida, Nasrun; Din, Muhammad; Amir, Andi Mattulada (Journal of Financial and Behavioural Accounting, 2024)
This study aims to (1) explain the implementation of the Regional Government Information System (SIPD), the Government Internal Control System (SPIP), and the Quality of Financial Reports (KLK); (2) assess the impact of the implementation of SIPD on KLK; and (3) evaluate the effect of the implementation of SPIP on KLK. This study uses the Partial Least Squares (PLS) method in Structural Equation Modeling (SEM) with WarpPLS 8.0 software, involving 128 respondents. The research findings show that (1) the majority of Regional Government Work Units support the implementation of SIPD and SPIP to improve KLK; (2) the implementation of SIPD has a positive and significant effect on KLK; and (3) the implementation of SPIP also has a positive and significant effect on KLK.